2020
DOI: 10.1111/acel.13119
|View full text |Cite
|
Sign up to set email alerts
|

Systematic age‐, organ‐, and diet‐associated ionome remodeling and the development of ionomic aging clocks

Abstract: Aging involves coordinated yet distinct changes in organs and systems throughout life, including changes in essential trace elements. However, how aging affects tissue element composition (ionome) and how these changes lead to dysfunction and disease remain unclear. Here, we quantified changes in the ionome across eight organs and 16 age groups of mice. This global profiling revealed novel interactions between elements at the level of tissue, age, and diet, and allowed us to achieve a broader, organismal view … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…Principal Component Analysis (PCA) shows organ-specific metallomic and isotopic signatures (Fig. 1b ) as described before 12 14 . The first principal component is driven oppositely by protein-bound transition metals (Fe, Zn, Se, Mn, Co, and Cu) and free alkali and alkaline earth metals (Ca, K, and Mg) (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Principal Component Analysis (PCA) shows organ-specific metallomic and isotopic signatures (Fig. 1b ) as described before 12 14 . The first principal component is driven oppositely by protein-bound transition metals (Fe, Zn, Se, Mn, Co, and Cu) and free alkali and alkaline earth metals (Ca, K, and Mg) (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Animal experiments revealed that zinc affects the extracellular matrix of the vagina. Also, in aging mice and rats, the tissue concentration of zinc and copper decreases [13][14][15]. Histological and histochemical pictures of vaginas from mice with a zinc-deficient diet look similar to ovariectomized animals.…”
Section: Introductionmentioning
confidence: 85%
“…Tissue levels of zinc and copper decrease with aging in animals [13][14][15], but previously no data has been available regarding animal or human vaginal tissues. However, in the human uterus (corpus) during menopause, copper levels were seen to rise as zinc levels fell [23].…”
Section: Discussionmentioning
confidence: 99%
“…ICP-MS has the ability to detect not only many metals and non-metals at very low concentration (such as part per trillion) but also different isotopes of the same element, whereas ICP-OES offers the advantages of lower cost and simplicity of acquisition and operation [ 34 , 35 ]. In recent years, both ICP-MS and ICP-OES have been successfully used for large-scale ionomic studies in yeast, plants, and animals, which demonstrate the power of ionomics to investigate new aspects of trace element metabolism and status [ 15 , 17 , 18 , 36 , 37 , 38 , 39 , 40 ].…”
Section: An Overview Of Ionomics and Its Application In Mammalsmentioning
confidence: 99%
“…Very recently, the ionomic profiles of eight organs throughout the lifespan of mice were quantified, which showed new interactions between elements at different levels [ 40 ]. The organ ionomes were stable throughout the entire lifespan, and aging was generally characterized by the reduced levels of elements and their increased variance.…”
Section: An Overview Of Ionomics and Its Application In Mammalsmentioning
confidence: 99%